Nilai Moral Jawara Banten Dalam Pendidikan Karakter Siswa - Nur Hidayat; Achmad Hufad; Suroso Mukti Leksono (Jurnal Ilmiah Wahana Pendidikan, 2022)
Jawara of a special position in Banten society. Jawara was part of the subculture in Banten society that has a special position other than "Kiai" and "Ulama". Jawara's position in Banten society had a strong influence that penetrates the boundaries of rural hierarchies in Banten, so that Jawara gets informal labeling by the people of Banten. The purpose of this study was to identify the moral values of Jawara Banten in the formation of students' character. The method used in this research was to use the literature review method. Based on the research, it can be said that the moral values of Banten's Jawara were positive in the formation of student character, namely: the values of discipline, independence, and hard work that can be realized in students' daily lives.